Fahr’s syndrome as a manifestation of autoimmune polyendocrine syndrome-1 and its unusual association with neuromyelitis optica spectrum disorder - Nawaz, Ahmad; Ahmad, Azba; Aslam, Ayesha; Bano, Safia; Numan, Ahsan; Sarmad, Eisham (Frontiers in Neuroscience, 2023)
Fahr’s syndrome, also known as bilateral striopallidodendate calcinosis, is a rare inherited neurodegenerative illness characterized by abnormal calcium deposition in several areas of the brain, resulting in a wide range of neuropsychological symptoms. Fahr’s syndrome, secondary to autoimmune polyendocrine syndrome type 1, which includes adrenal insufficiency and mucocutaneous candidiasis in addition to hypoparathyroidism, is exceedingly rare. No case report has been documented to date to show the co-occurrence of Fahr’s syndrome and neuromyelitis optica spectrum disorder. Here, we discuss the case of a 30-year-old man with a previous history of seizures and symptoms of ectodermal dystrophy presented with seizures, left-sided hemiparesis, dysarthria, and other characteristics indicative of severe hypocalcemia. The neuroimaging findings strongly suggested Fahr’s syndrome, with radiographic evidence of Neuromyelitis optica spectrum disorder as longitudinal extensive transverse myelitis in the cervical spinal cord, high titers of serum aquaporin-4 antibodies, and demyelinating neuropathy on nerve conduction studies. This distinct neuropsychological presentation and neuroimaging findings led to the diagnosis of Fahr’s syndrome as a result of hypoparathyroidism caused by autoimmune polyendocrine syndrome type 1 with cooccurrence of neuromyelitis optica spectrum disorder. The patient’s clinical symptoms improved considerably after he was treated based on a provisional diagnosis. The clinical importance of our case is significant for both neuropsychiatrists and endocrinologists, as autoimmune polyendocrine syndrome should be considered as the etiology of Fahr’s syndrome. This case report also aims to report this unusual association of Neuromyelitis optica spectrum disorder with Fahr’s syndrome to give the future prospective to know whether this association is incidental or there is a missing link between these two different disorders.